2015
DOI: 10.7314/apjcp.2015.16.1.339
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between Hsa-Mir-499 rs3746444 Polymorphism and Cancer Risk: Meta-analysis Findings

Abstract: Epidemiologic findings concerning the association between the hsa-mir-499 rs3746444 A>G polymorphism and cancer risk have yielded mixed results. We aimed to investigate the association by performing a meta-analysis of all available studies. We searched PubMed and EMBASE for studies published up to November 2014, using odds ratios (ORs) with 95% confidence intervals (CIs) to assess the strength of any association. The BenjaminiHochberg (BH) method was used to correct the p values for multiple comparisons. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…40 Although some meta-analytic results showed that the association was more notable in Asian populations than in Caucasian populations, 32,41 other meta-analyses found no significant association between rs3746444 and BC risk. 34,42 In our study, the results suggested that individuals who carried rs3746444 AG/GG genotypes had an increased BC risk. Moreover, the rs3746444 AG/GG genotypes were revealed to be associated with an increased risk of moderate-severe vascular invasion and positive HER-2 in BC.…”
Section: Discussionsupporting
confidence: 52%
“…40 Although some meta-analytic results showed that the association was more notable in Asian populations than in Caucasian populations, 32,41 other meta-analyses found no significant association between rs3746444 and BC risk. 34,42 In our study, the results suggested that individuals who carried rs3746444 AG/GG genotypes had an increased BC risk. Moreover, the rs3746444 AG/GG genotypes were revealed to be associated with an increased risk of moderate-severe vascular invasion and positive HER-2 in BC.…”
Section: Discussionsupporting
confidence: 52%
“…Several meta-analyses have explored the association between the miR-499 rs3746444 polymorphism and cancer risk and it is difficult to judge if the analysis without studies departing from HWE would be more valid or not. An overall meta-analysis by Jiang et al ( 2015 ) demonstrated a borderline association (TC+CC vs. TT: OR = 1.15, P = 0.04). However, the association disappeared (TC+CC vs. TT: OR = 1.18, P = 0.21) when studies departing from HWE were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of mir-499 rs3746444 C-allele carriers with an increased susceptibility of cancer have been identified in some meta-analysis [8][9][10]12,13]. Of late, meta-analyses have tried to determine the correlation between this SNP and the risk of GC [8][9][10][11][12][13]32,33]. And all of them have obtained the null association, which maybe due to the limited literatures.…”
Section: Discussionmentioning
confidence: 99%
“…Rs3746444 T>C SNP is located in mir-499 and extensively studied the association of this SNP with cancer risk. Meta-analyses have established the correlation between this SNP and the risk of overall cancer [8][9][10][11][12][13]. Most of these findings suggested that rs3746444 C-allele carriers appeared to get an increased susceptibility of cancer [8][9][10]12,13].…”
Section: Introductionmentioning
confidence: 99%